Mechanisms and conditions that affect phase inversion processes: A review. (5th October 2020) - Maffi, Juan M.; Meira, Gregorio R.; Estenoz, Diana A.
Abstract: The phenomenon of phase inversion occurs in liquid‐liquid dispersions found in a variety of chemical engineering fields. From simple oil‐water mixtures to complex polymeric systems, the operating variables that affect this physical phenomenon are discussed in this work. The contribution on this matter by a large number of researchers is critically assessed, outlining both coherent and conflicting results. A detailed review of the mechanisms by which phase inversion takes place is also provided. While this subject has been studied for the past 50 years, this multivariate nonlinear process is not yet comprehensively understood, and this review article aims to describe the conclusions so far reached to provide insight for future research.